The importance of FDG-PET/CT parameters for the assessment of the immune status in advanced HNSCC. Issue 4 (August 2020) - Ohashi, Toshimitsu; Terasawa, Kousuke; Aoki, Mitsuhiro; Akazawa, Takashi; Shibata, Hirofumi; Kuze, Bunya; Asano, Takahiko; Kato, Hiroki; Miyazaki, Tatsuhiko; Matsuo, Masayuki; Inoue, Norimitsu; Ito, Yatsuji
Abstract: Objective: Cancer cells secrete large amounts of lactic acid via aerobic glycolysis. We have shown that lactic acid plays an important role as a proinflammatory and immunosuppressive mediator and promotes tumor progression. Fluorine-18 fluorodeoxyglucose (FDG) uptake detected by positron emission tomography/computed tomography (PET/CT) is considered as a good indicator of aerobic glycolysis in cancer. In this study, we examined the relationships between systemic inflammatory parameters and FDG-PET/CT parameters in advanced head and neck squamous cell carcinoma (HNSCC). Furthermore, we investigated the relationships between FDG-PET/CT parameters and M2-macrophage polarization in HNSCC by assessing the ratio of CD163, a M2-macrophage marker, to CD68, a pan-macrophage marker. Methods: This study included 73 advanced HNSCC patients. We assessed the C-reactive protein (CRP) level, white blood cell (WBC) count, neutrophil count, lymphocyte count, and monocyte count as systemic inflammatory markers. Additionally, we assessed the maximum standardized uptake value (SUVmax ), mean SUV (SUVmean ), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) as FDG-PET/CT parameters. Results: The CRP level, WBC count, and neutrophil count were correlated with whole-body FDG-PET/CT parameters. The CD163/CD68 ratio was correlated with SUVmax and SUVmean. Our results suggest that systemic inflammation, which is associated with neutrophils, develops in patients with HNSCC having tumors with a larger volume and increased glucose uptake and that M2-macrophage polarization is promoted in HNSCC with increased glucose uptake, SUVmax, and SUVmean. FDG-PET/CT has the potential to reflect cancer-related chronic inflammation and immunosuppressive conditions in cancer patients. Conclusions: FDG-PET/CT parameters appear to be useful in assessing the immune status in HNSCC.